2015
DOI: 10.1093/ejcts/ezv052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulmonary hypertension on ovine tricuspid annular dynamics

Abstract: The changes in tricuspid annular conformation, contractility and its 3D geometry observed during acute ovine PHT may help in the design of new pathology-specific tricuspid annular rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Knio et al [ 17 ] used real-time 3D transesophageal echocardiography (TEE) to quantify the dimensions of the tricuspid annulus and analyze its geometric changes over the course of the cardiac cycle, and their analysis demonstrated that the tricuspid annulus is a nonplanar and dynamic structure. Malinowski et al [ 18 ] found the tricuspid annulus is a saddle-shaped nonplanar structure with 2 horns in the anteroseptal and posterior regions. During acute PH and LV pressure overload, the TA dilates along all annular regions while the 3D annular geometry is essentially preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Knio et al [ 17 ] used real-time 3D transesophageal echocardiography (TEE) to quantify the dimensions of the tricuspid annulus and analyze its geometric changes over the course of the cardiac cycle, and their analysis demonstrated that the tricuspid annulus is a nonplanar and dynamic structure. Malinowski et al [ 18 ] found the tricuspid annulus is a saddle-shaped nonplanar structure with 2 horns in the anteroseptal and posterior regions. During acute PH and LV pressure overload, the TA dilates along all annular regions while the 3D annular geometry is essentially preserved.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of in-vivo studies of the TV annulus, measurements are generally made using MRI, 2DE/3DE, or CT (Figure 7a) [97,98]. A study by Hammarström et al (1991) [97] used 2DE to measure human annulus parameters with three primary observations: (i) an average annular diameter (between diastole and systole) of 22.5 mm, (ii) the greatest motion occurring along the lateral point of the TV annulus, and (iii) a hinge-point of the annulus movement occurring on the septal side.…”
Section: In-vivo and In-vitro Investigationsmentioning
confidence: 99%
“…These observations were later reaffirmed, and more details of the annulus movement were provided through other human in-vivo studies. For example, Ring et al (2012) [98] used 3DE to quantify: (i) AP and SL average diameters of 41.15 mm and 33.75 mm, respectively, (ii) heights from diastole to systole of 4.2 mm to 5.5 mm, respectively, (iii) areas from diastole to systole of 1145 mm 2 to 1049 mm 2 , respectively, (iv) perimeters from diastole to systole of 124 mm to 120 mm, respectively, and (v) eccentricity values from diastole to systole of 1.20 to 1.29, respectively. Regarding the annular movement, during diastole the annulus has a more circular shape, while during systole the annulus becomes more elliptical, as shown through the observed eccentricity values.…”
Section: In-vivo and In-vitro Investigationsmentioning
confidence: 99%
“…All data were recorded with Sonometrics Digital Ultrasonic Measurement System DS3 as previously reported [11]. Data from 3 consecutive heart cycles acquired at 128 Hz during sinus rhythm and steady-state haemodynamic conditions were merged to yield 3-dimensional co-ordinates of each sonomicrometry crystal for Baseline and each step of annular reduction.…”
Section: Data Acquisitionmentioning
confidence: 99%